Sexual Compulsive Symptoms and General Psychopathology: Exploring the Role of Sexual Orientation in Men - Testa, Giulia; Chiclana Actis, Carlos; Checa Ojeda, Nicolás (Sexual Health & Compulsivity, 2024)
Sexual compulsivity symptoms are more common in men than in women. However, there is less evidence on the role of other relevant variables such as sexual orientation and general psychopathology. The present study aimed to assess the relationship between psychopathological and sexual compulsivity symptoms in heterosexual, gay, or bisexual men. A total of 564 adult’s men completed an assessment including sociodemographic variables, the Sexual Compulsivity Scale (SCS), and the Symptom Checklist-90-Revised (SCL-90-R). Results showed no significant differences in the SCS across sexual orientation groups. However, gay participants showed higher SCL-90-R general severity index (GSI), somatization, interpersonal sensitivity, anxiety, phobic anxiety, and psychoticism subscales compared to heterosexual men. Bisexual men had higher anxiety levels than gay men. Positive correlations between the SCS and SCL-90-R scores were present, regardless of sexual orientation. Multiple linear regression analysis identified GSI scores as predictors of SCS. In contrast, sexual orientation and age did not predict SCS. These findings suggest that there is an association between general psychopathology and symptoms of sexual compulsivity which is independent of sexual orientation, at least among men. Further research including clinical samples and women is needed to increase understanding in this field.
Keywords: sexual compulsive symptoms; general psychopathology; role of sexual orientation; Men